Self-Sacrifice As Seen in Harry Potter and The Philosopher’s Stone Movie - Andries, Fivy A.; Warouw, Gisella L. G.; Maukar, Merlin M.; Tulus, Arie (Journal of English Culture, Language, Literature and Education, 2024)
The purpose of this study is to reveal Self-Sacrifice as Seen in Kloves's Harry Potter and the Philosopher's Stone. In conducting the study, the writer delimited this study only in revealing self-sacrifice using descriptive qualitative method. In analyzing the data the writer used psychological approach based on the theory of Carl Jung. Jung said that we must deal with three powerful archetypes that compose the self there are the Shadow, the Anima, and the Persona. The data taken from the Harry Potter and the Philosopher's Stone movie script by Steve Kloves based on the novel by J.K. Rowling. After analyze the movie script the writer may concluded that the characters in Harry Potter and the PhilosopherÃ¢â‚¬â„¢s Stone indeed their self-sacrifice through their Sincerity of Love which is anima; Willingness to make Commitment and Willingness to tell Lies which are shadow; and Willingness to take a Risk which is persona as the components of self-sacrifice. These four types of self-sacrifice clearly describe in the movie. Through these findings, how sincere and valuable are self-sacrifice that felt by the main character Harry Potter and experienced by his family and friends seen in Harry Potter and the Philosopher's Stone Movie. Ã‚Â